2021
DOI: 10.1111/jfbc.13889
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharides ameliorate LPS‐induced inflammation of RAW264.7 cells and modify the behavioral score of peritonitis mice

Abstract: In the present study, the anti-inflammatory effect of Lycium barbarum polysaccharide (LBP) and the possible molecular mechanism thereof were examined, so as to perceive the pharmacological action of LBP. With acute peritonitis in mice as the inflammatory model, the protective effect of LBP on peritonitis mice was evaluated by recording the effect of behavioral scores, studying the pathological damage of intestine and liver, and detecting the levels of inflammatory cytokines. Additionally, by establishing an li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In our experimental system, the Nfkb transcription factor pathway was significantly activated. This is consistent with previous reports as the Nfkb transcription factor pathway is also activated in the LPS-mediated peritonitis model [ 14 , 28 ]. Hence, the Nfkb transcription factor pathway may play an essential role in the occurrence of LPS-mediated peritonitis.…”
Section: Discussionsupporting
confidence: 94%
“…In our experimental system, the Nfkb transcription factor pathway was significantly activated. This is consistent with previous reports as the Nfkb transcription factor pathway is also activated in the LPS-mediated peritonitis model [ 14 , 28 ]. Hence, the Nfkb transcription factor pathway may play an essential role in the occurrence of LPS-mediated peritonitis.…”
Section: Discussionsupporting
confidence: 94%
“…The anti-inflammatory effects of LBP were further supported by reduced TNF-α and IL-1β mRNA expression in astrocytes and microglia in the LBP-treated group, and inhibition of P38 MAPK activation [66]. In ad- dition, Liu et al [80] found that LBP pretreatment significantly decreased the secretion of inflammatory factors in lipopolysaccharide-induced peritonitis mice models (Fig. 1, Table 2 (Ref.…”
Section: Lycium Barbarum Improves the Inflammatory Responsementioning
confidence: 83%
“…By regulating macrophage polarization, it can reduce the expression levels of inflammatory cytokines and NO, enabling it to exert anti-inflammatory effects. 38 4.1.4. Extractive Ingredients of Turmeric.…”
Section: Extractive Ingredients Of Hippophae Rhamnoidesmentioning
confidence: 99%
“…A low concentration of Lycium barbarum polysaccharides increases the expression of the M2 macrophage marker CD206, and a high concentration of Lycium barbarum polysaccharides decreases the expression of the M1 macrophage marker CD86. By regulating macrophage polarization, it can reduce the expression levels of inflammatory cytokines and NO, enabling it to exert anti-inflammatory effects …”
Section: Effect Of Ifmh In Regulating Macrophage Polarization On Athe...mentioning
confidence: 99%
See 1 more Smart Citation